Characteristics and Treatment Challenges of Patients With Comorbid ADHD and Psychosis: A Cross-Sectional Study in Early Intervention Services - Salam Fahad; Nismen Lathif (BJPsych Open)
Aims: Comorbid attention deficit hyperactivity disorder (ADHD) and psychosis present significant challenges in Early Intervention in Psychosis (EIP) services. This study examined the prevalence, diagnostic patterns, and treatment challenges of this comorbidity within EIP teams in Halton and Warrington, UK.